2016
DOI: 10.1021/acsami.6b05324
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Fast Growth and Forced Jumping of Stretched Droplets on Nanostructured Microporous Surfaces

Abstract: Superhydrophobic nanostructured surfaces have demonstrated outstanding capability in energy and water applications by promoting dropwise condensation, where fast droplet growth and efficient condensate removal are two key parameters. However, these parameters remain contradictory. Although efficient droplet removal is easily obtained through coalescence jumping on uniform superhydrophobic surfaces, simultaneously achieving fast droplet growth is still challenging. Also, on such surfaces droplets can grow to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…In principle, any sub-microscale structures with a small feature size (tip size and interspace) and a certain height (or depth) can become effective candidates for creating CMDSP surfaces. In fact, except for arrays of closely packed nanotips, including nanocones, [22,27,50,69,70] nanoneedles, [21,28,31,66,71] nanopencils, [23] and tip-like nanotubes, [72,73] other architectures such as nano wires, [24,74] nanosheet arrays, [20,29,62,75] nanorod-capped nano pores, [68,76] the porous structure of nanoparticles, [67] nanoparticle aggregates, [73,[77][78][79][80] and two-tier structures [25,57,63,[81][82][83][84][85][86][87][88][89] have all been verified to be effective in endowing material surfaces with the desired CMDSP functionality as long as they follow these basic construction rules.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
“…In principle, any sub-microscale structures with a small feature size (tip size and interspace) and a certain height (or depth) can become effective candidates for creating CMDSP surfaces. In fact, except for arrays of closely packed nanotips, including nanocones, [22,27,50,69,70] nanoneedles, [21,28,31,66,71] nanopencils, [23] and tip-like nanotubes, [72,73] other architectures such as nano wires, [24,74] nanosheet arrays, [20,29,62,75] nanorod-capped nano pores, [68,76] the porous structure of nanoparticles, [67] nanoparticle aggregates, [73,[77][78][79][80] and two-tier structures [25,57,63,[81][82][83][84][85][86][87][88][89] have all been verified to be effective in endowing material surfaces with the desired CMDSP functionality as long as they follow these basic construction rules.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
“…There is research gap when it comes to the collection of produced water vapors in recently developed solar steam generation devices. However, the filmwise and dropwise condensation on flat and nano-/micro-structured surfaces is a well-studied phenomenon, and we can take advantage from the development of nanotechnology to design an appropriate surface, which can effectively enhance the condensation process without altering the transmittance of the cover [93]. Our previous studies have shown the role of surface wettability to achieve enhanced dropwise condensation, where droplet growth and efficient condensate removal are two key contributing factors (Figure 9a).…”
Section: Condensation and Collectionmentioning
confidence: 99%
“…This new pressure gradient contributes to the driving force that leads to droplet discharge. [ 106 ]…”
Section: Coalescence‐induced Jumping‐droplet Condensationmentioning
confidence: 99%